Le contrôle social des mineurs par le logement dans les bassins houiller européens est-il un mythe ? - Guy Baudelle (Amnis)
Miners’ housing built by the operators in the Western European coalfields was most often seen as an expression of social control. A less ideological view shows that employers' housing primarily aimed at increasing the workforce. Its possible instrumentalization for purposes of social control was only a secondary result of its technical function. Considering it a tool of repression is incompatible with the productive imperative. More generally, paternalism was a system with an essentially industrial vocation. This interpretation is mainly illustrated by the case of the former Nord and Pas-de-Calais coalfield (1720-1990).